2019
DOI: 10.1242/dmm.040642
|View full text |Cite
|
Sign up to set email alerts
|

Notch4 activation aggravates NF-kappa B mediated inflammation in HIV-1 associated Nephropathy

Abstract: Notch pathway activation plays a central role in the pathogenesis of many glomerular diseases. We have previously shown that Notch4 expression was upregulated in various renal cells in human immunodeficiency virus (HIV)-associated nephropathy (HIVAN) patients and rodent models of HIVAN. In this study, we examined whether the Notch pathway can be distinctly activated by HIV-1 gene products and whether Notch4, in particular, can influence disease progression. Using luciferase reporter assays, we did not observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Studies done in Notch3 ‐deficient mice with the UUO model found less tubular injury and significantly reduced interstitial collagen deposition 38,43,44 . Similarly, Notch2‐ and Notch4‐ deficient mice are protected from several renal‐related injuries, such as folic‐acid or immunodeficiency virus‐associated nephropathy 39,45 . In our study, total NOTCH2 and NOTCH4 receptor protein levels are decreased in Dlk1 ‐null mice as compared to WT, indicating that this could be an effect of Dlk1 deletion or of concomitant Dlk2 overexpression.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Studies done in Notch3 ‐deficient mice with the UUO model found less tubular injury and significantly reduced interstitial collagen deposition 38,43,44 . Similarly, Notch2‐ and Notch4‐ deficient mice are protected from several renal‐related injuries, such as folic‐acid or immunodeficiency virus‐associated nephropathy 39,45 . In our study, total NOTCH2 and NOTCH4 receptor protein levels are decreased in Dlk1 ‐null mice as compared to WT, indicating that this could be an effect of Dlk1 deletion or of concomitant Dlk2 overexpression.…”
Section: Discussionsupporting
confidence: 68%
“…38,43,44 Similarly, Notch2-and Notch4-deficient mice are protected from several renal-related injuries, such as folic-acid or immunodeficiency virus-associated nephropathy. 39,45 In our study, total NOTCH2 and NOTCH4 receptor protein levels are decreased in Dlk1-null mice as compared to WT, indicating that this could be an effect of Dlk1 deletion or of concomitant Dlk2 overexpression. Recent findings indicate that both DLK1 and DLK2 can modulate the activity of the four NOTCH receptors, 46,47 albeit in a different manner.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…An important aspect of this process concerns the immunological synapses that occur between neighboring cells. We identified the upregulation of Notch pathway-related genes ROBO1, DLL4, DLL1, GATA2, JAG1 and MDK (GO:0007219 “Notch signaling pathway”), which act as co-activators in the stimulation of the NF-κB pathway, which induces IL-2 production, responsible for proliferation and activation of CD4+ T lymphocytes and is associated with latency suppression mechanisms and initiation of viral transcription [ 42 , 47 ]. The NF-κB (nuclear factor kappa B) pathway is exploited by HIV-1 to activate its transcription, by having NF-κB binding sites in its long terminal repeats (LTRs) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling is a key regulator in multiple diseases ( 44 , 45 ). NF-κB is an evolutionarily conserved transcription factor that controls the expression levels of various cytokines and adhesion molecules, and is involved in responses to infection, stress and damage ( 46 ).…”
Section: Discussionmentioning
confidence: 99%